Peran Pemasaran Media Sosial dalam Membentuk Perilaku Pembelian Konsumen Sebagai Pertimbangan dalam Studi Kelayakan Bisnis: Studi pada Toko Teman Hijrahku - Wiwi Astiawati; Fitrianita Fitrianita; Mutmainnah Mutmainnah; Hasni Hasni (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to analyze the role of social media in shaping consumer behavior as a consideration in business feasibility studies, with a case study of Toko Teman Hijrahku. The method used is a qualitative approach through documentation and in-depth interviews with the owner and consumers. The results show that social media not only increases purchase intention but can also be considered as a tool for business feasibility analysis, especially for MSMEs in the digital era. Thus, social media becomes an essential part of modern marketing strategies that support business growth and sustainability